Pengembangan Sistem Informasi Kesiswaan dan Alumni pada Lembaga Pendidikan Islam di Kabupaten Sidoarjo - Huda, Muhammad Nuril; Mansyuri, Arif (Jurnal Administrasi Pendidikan Islam, 2024)
The lack of data on student affairs and synchronization with alumni is one of the problems in education that educational institutions are not aware of. The research aims to create a student and alumni management information system that is integrated with data when alumni graduate. System development uses the ADDIE model with a web system basis, PHP programming, and MySQL database. The Student and Alumni Management information system can be used properly with various data features in it such as student biodata, parental data, school origin data, current class data, post-graduation data, teacher data, class data, school year data, violations and achievements, coaching, and all reports can be printed out in pdf format or exported in xls format.